The Survivor: A Clinical Case of Tetanus in a Non-Immunized, Parenteral Drug User, Former Female Convict with HIV and HCV - Nancy Vicente-Alcalde (Vaccines, 2020)
Tetanus is a serious and potentially fatal systemic disease, caused by the bacterium Clostridium tetani. It is estimated that 1 million cases occur worldwide annually. Immunization programs have drastically decreased tetanus in developed countries, and the sporadic cases have been linked to injecting drug users (IDUs), immunosuppressed individuals, or those older than 65 without complete vaccination. Regrettably, it is still endemic in under-developed countries. In Spain, an average of 10 cases are notified each year, especially affecting those older than 65. The present article describes a case of a 48-year-old Spanish woman, an ex-convict and IDU with infection antecedents of Human Immunodeficiency Virus (HIV) and Hepatitis C (HCV), who was admitted to the Emergency Department of a University Hospital with cervical rigidity and trismus. In a few hours, a neurological and respiratory deterioration was observed, resulting in admittance to the intensive care unit under the suspicion of a generalized tetanus infection. The treatment included hemodynamic support and respiratory therapy, antibiotics, muscle relaxants, sedatives, and tetanus immunoglobulin. Her stay in the ICU lasted 47 days. The clinical suspicion, the antecedents of risk, and the verification of the vaccination records should provide early guidance for diagnostics and the establishment of a treatment in these cases.